2017
DOI: 10.1111/bju.13836
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐stratification based on magnetic resonance imaging and prostate‐specific antigen density may reduce unnecessary follow‐up biopsy procedures in men on active surveillance for low‐risk prostate cancer

Abstract: At least one out of five men on AS with Gleason score 3 + 3 prostate cancer at diagnostic TRUS-Bx show Gleason score upgrading based on first MRI ± TBx at baseline, confirmatory or surveillance biopsy. Men with a PI-RADS score of 1-3 and PSA-D of <0.15 ng/mL did not show Gleason score upgrading at MRI ± TBx or TRUS-Bx at each time point of surveillance. Thus risk-stratification based on PI-RADS and PSA-D may reduce unnecessary follow-up biopsy procedures in men on AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
57
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 39 publications
3
57
2
6
Order By: Relevance
“…This is no longer the case when MRI risk stratification is taken into account. Other studies have shown that ~10% of men on active surveillance with no visible MRI lesion will be found to have upgrading if routine confirmatory biopsies are performed . In the present study, only 1.8% of patients with negative MRI were found to have upgrading on confirmatory biopsy.…”
Section: Discussioncontrasting
confidence: 66%
“…This is no longer the case when MRI risk stratification is taken into account. Other studies have shown that ~10% of men on active surveillance with no visible MRI lesion will be found to have upgrading if routine confirmatory biopsies are performed . In the present study, only 1.8% of patients with negative MRI were found to have upgrading on confirmatory biopsy.…”
Section: Discussioncontrasting
confidence: 66%
“…PSAD has been well reported to be a marker of progression in AS . Remarkably the threshold value of 0.15 ng/mL/mL has been found independently in many of these studies . In our present analysis, the presence of a baseline MRI lesion was not predictive of progression and we had too few cases to sub‐analyse differences between Likert 3, 4 and 5 lesions.…”
Section: Discussionmentioning
confidence: 51%
“…However, strikingly, many men with CPG2 disease (32/37 in the UK series, >85%) actually did not progress. PSAD has been well reported to be a marker of progression in AS . Remarkably the threshold value of 0.15 ng/mL/mL has been found independently in many of these studies .…”
Section: Discussionmentioning
confidence: 82%
“…In our study population, this would have resulted in a 20% decrease in the number of biopsies performed, and only 4% of significant cancers would have escaped diagnosis. If slightly different criteria suggested by other authors were applied to our cohort (i.e., PIRADS = 3 and PSAD < 0.15) [14,16,17], it would result in a 50% reduction in the number of biopsies but would also miss 21% of significant cancers. We speculate that the discrepancy between this finding and those reported in other papers might be explained by the performance of the mpMRI [3,18,19].…”
Section: Discussionmentioning
confidence: 99%